The Effect of Health Education Using a Flip Chart on Compliance with Fe Tablet Consumption in Pregnant Women in the Working Area of the South City Health Center - Sulmina; Ridha Hafid; Siti Hajar Salawali (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Compliance of pregnant women in taking Fe tablets is an important effort in preventing anemia during pregnancy, but the level of compliance is still relatively low due to the lack of understanding of pregnant women regarding the benefits and proper ways to consume Fe tablets. Health education using flip chart media is one of the methods that can increase understanding and encourage changes in compliance behavior. This study aims to determine the effect of health education using flip sheets on compliance with Fe tablet consumption in pregnant women in the working area of the South City Health Center. The results of the Wilcoxon test obtained a p value = 0.000 (p < 0.05), which shows a significant influence of health education using flip sheets on compliance with Fe tablet consumption in pregnant women. It was concluded that health education using flip sheets was effective in increasing compliance with Fe tablet consumption. It is recommended that the South City Health Center optimize the use of flip sheet media in antenatal care services.